The Concept of Birul Walidain in the View of M. Quraish Shihab in Tafsir Al Misbah Surah Luqman Verse 14 - A’idatun Nisa; Muthoifin Muthoifin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this research is to find out how M. Quraish Shihab views in his interpretation of Al-Misbah surah Luqman verse 14 about the concept of birrul walidain or God's command to his people to serve their parents. This research method uses a qualitative type, by examining in depth the contents of the interpretation in the Kitab al-Misbah and other books related to the research, the analysis uses analytical content and a religious normative approach. The results of this study indicate that the concept of birrul walidain according to M. Quraish Shibab emphasizes human beings: 1). To always be more devoted to parents after obeying Allah, 2). Devotion to parents is obligatory, and a great sin for those who disobey them, 3). Birrul walidain is a field of charity to enter heaven, 4). Devotion to parents, whether alive or dead by praying for them, 5). Including having to be devoted to him even though different religions and beliefs.